Sustainable Development Goals, public policies and attention in Mexico (Dissertare, 2021)
Mexico is making efforts to achieve the Sustainable Development Goals of the 2030 Agenda. To do this, it implements directly or indirectly public policies for care, related to the provision of everything necessary for the health, maintenance, protection and well-being of people. However, there is no recognition of care in Mexican laws and regulations, except for some specifications that limit the operation of public programs and actions for the direct promotion of care. This document aims to analyze the evolution in compliance with the SDGs that are related to care during the six-year period 2012-2018 in Mexico; which allows an approximation towards the impact achieved in this matter as a result of the implementation of said objectives. An analysis methodology with a documentary design was followed, which involved a bibliographic review based on data available in the Mexico 2030 Agenda of the SDGs on indicators related to care. It was observed that public programs of a social nature oriented towards sustainable development objectives have had limited but positive effects. The least advances are generated in poverty and gender equality; while the main achievements are in education, health, food and social security issues. Thus, the progress achieved particularly favors the care of children in early childhood, who are net claimants of care and future direct or indirect providers.